The prognostic utility of prehospital qSOFA in addition to emergency department qSOFA for sepsis in patients with suspected infection: A retrospective cohort study - Ayaka Saito; Itsuki Osawa; Junichiro Shibata; Tomohiro Sonoo; Kensuke Nakamura; Tadahiro Goto (PLoS ONE, 2023)
Background The quick sequential organ failure assessment (qSOFA) was widely used to estimate the risks of sepsis in patients with suspected infection in the prehospital and emergency department (ED) settings. Due to the insufficient sensitivity of qSOFA on arrival at the ED (ED qSOFA), the Surviving Sepsis Campaign 2021 recommended against using qSOFA as a single screening tool for sepsis. However, it remains unclear whether the combined use of prehospital and ED qSOFA improves its sensitivity for identifying patients at a higher risk of sepsis at the ED. Methods We retrospectively analyzed the data from the ED of a tertiary medical center in Japan from April 2018 through March 2021. Among all adult patients (aged ≥18 years) transported by ambulance to the ED with suspected infection, we identified patients who were subsequently diagnosed with sepsis based on the Sepsis-3 criteria. We compared the predictive abilities of prehospital qSOFA, ED qSOFA, and the sum of prehospital and ED qSOFA (combined qSOFA) for sepsis in patients with suspected infection at the ED. Results Among 2,407 patients with suspected infection transported to the ED by ambulance, 369 (15%) patients were subsequently diagnosed with sepsis, and 217 (9%) died during hospitalization. The sensitivity of prehospital qSOFA ≥2 and ED qSOFA ≥2 were comparable (c-statistics for sepsis [95%CI], 0.57 [0.52–0.62] vs. 0.55 [0.50–0.60]). However, combined qSOFA (cutoff, ≥3 [max 6]) was more sensitive than ED qSOFA (cutoff, ≥2) for identifying sepsis (0.67 [95%CI, 0.62–0.72] vs. 0.55 [95%CI, 0.50–0.60]). Using combined qSOFA, we identified 44 (12%) out of 369 patients who were subsequently diagnosed with sepsis, which would have been missed using ED qSOFA alone. Conclusions Using both prehospital and ED qSOFA could improve the screening ability of sepsis among patients with suspected infection at the ED.